The perception and association between depression and academic stress among female undergraduate nursing students: a cross-sectional study - Andargeery, Shaherah Yousef (Frontiers in Public Health, 2024)
Academic demands and stressors put nursing students at increasing risk of depression. The aims of the study examine the perceived level of depression and academic stress and investigate the association between these variables among nursing students in Saudi Arabia. A cross-sectional design was used in this study. Data was collected using depression subscale from DASS-21 scale and the Academic Stress Inventory scale. A total of 237 students participated in the study. Nursing students perceived normal to mild levels of depression. Students perceived moderate levels of academic stress in all subscales, except for time management and test stress which were high. All academic stress subscales had a positive statistically significant correlation with depression. The regression model explains 49.0% of the variance in the depression scale and indicated that the main significant predictor of depression is studying in group stress, followed by self-inflected stress, study year, and sleep problem. The mean score of depression for first year students was significantly different than students in other study years. Nurse educators should facilitate group formation and teach students about time-management, problem-solving, negotiation, and coping strategies to deal with academic expectations and demanding situations. Understanding the causes, limiting the exposure to negative influences, and seeking support as needed are important. To enhance the quality of sleep, students should maintain a consistent sleep schedule, while avoiding stimulating activities before bedtime. Future research should focus on a longitudinal study and other variables such as quality of life, satisfaction with the quality of teaching, and support from others.